A CRITICAL DISCOURSE ANALYSIS OF IDEOLOGY AND MEANING IN SELECTED NOVELS OF CHINUA ACHEBE (2011)
Most previous studies on Chinua Achebe's novels have largely concentrated on thematic preoccupations, especially inter-cultural conflicts in Africa. Some of the works focus on ideology and meaning with emphasis on cultural nationalism. Nevertheless, they have not yet objectified the relationship between the ideological contents of Achebe‟s novels and the discourse patterns reflected in the novels. This study, therefore, critically investigates more of the ideologies and underlying meanings mirrored in three of Achebe's novels, the objective being to highlight this relationship and their implications for nation-building in Nigeria. The study adopts a theoretical framework that combines Van Djik's model of Critical Discourse Analysis (CDA) with Michael Halliday's Systemic Functional Theory. The former enhances a broad social, cognitive and political interpretation of underlying ideologies in texts, while the latter lays emphasis on meaning. The framework facilitates the identification of largely socio-political ideologies and implicit meanings reflected in texts. The purposive sampling technique was applied to select Achebe's Things Fall Apart (TFA), A Man of the People (AMOP), and Anthills of the Savannah (AOS), perceived to be richer in ideological and implicit meanings than his other novels. One thousand, one hundred and seventy-two sentences with salient ideological and/or implicit meanings were identified in the texts out of which 250, chosen by means of simple random sampling, were analysed. A content analysis of these sentences covered the morphological, lexical, syntactic, rhetorical, and semantic levels. Some of the ideological contents in the selected sentences in the novels are despotism, chauvinism, and racism, the first of which is the central discourse field of the three novels. This embodies a dictatorial right-wing socio-political ideology that characterises military and civilian rules in Africa. Socio-culturally, despotism manifests in the patriarchal leadership system in which women and children are respectively at the mercy of their husbands and fathers as exemplified by Okonkwo's household in TFA. While this form of leadership is criticised in the novels for its multiple demerits like imposition, intolerance, subjugation and bullying, the left-wing socio-political ideology of participatory democracy is implicitly foregrounded, because it promotes a general positive attitude to life. At the lexical and morphological levels, Achebe achieves these elements by means of compounding ("big-chief"), neologisms ("negrophobist") and lexical metaphors ("national cake, "the roaring flame"). Achebe also passionately faults despotism and other right-wing ideologies at the syntactic and rhetorical levels by means of topicalisation ("women are their own worst enemies"); nominalisation ("worshipping a dictator") and passive syntax ("speeches made in vernacular were liable to be distorted and misquoted in the press"), to give the major underlying message that democracy is the only acceptable socio-political ideology. Several instances of ambiguity polarise some implicit meanings in the novels. For example, an ambiguous expression like "all of you" intratextually, in TFA, refers to the tortoise or a group of birds to signify credulity or greed. The texts also reflect insinuations ("it is in the place of the poor man to make a visit to the rich who holds the yam and the knife") that implicitly highlight the values of silence, wisdom, and sensible socio-political agitation as largely reflected in AOS and AMOP. Achebe's TFA, AMOP and AOS contain profound implicit and largely socio-political ideological meanings, which Nigeria as a nation can appropriate to make her democracy truly participatory. The analysis of the texts has also confirmed that a CDA unearths such meanings.